2001
DOI: 10.1017/s0317167100052525
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Clinical Neurosciences A Systematic Review of the Use of Triptans in Acute Migraine

Abstract: ABSTRACT:Objective:A systematic review of the literature was undertaken, to consolidate evidence concerning the efficacy and safety of triptans currently available in Canada (sumatriptan, rizatriptan, naratriptan, zolmitriptan), and to provide guidelines for selection of a triptan.Methods:Data from published, randomized, placebo-controlled trials were pooled and a combined number needed to treat (NNT) and number needed to harm (NNH) was generated for each triptan. Direct comparative trials of triptans were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 57 publications
6
45
0
Order By: Relevance
“…A third metanalysis performed in Canada in 2001, including the available triptans at that time in Canada (sumatriptan, rizatriptan, zolmitriptan, and naratriptan) also calculated the NNT [Gawel et al, 2001] and showed similar results to the first two metanalysis. Finally, Ferrari et al published a metanalysis that included 53 clinical trials (12 unpublished) involving 24,089 patients [Ferrari et al, 2001].…”
Section: Selecting a Triptanmentioning
confidence: 70%
“…A third metanalysis performed in Canada in 2001, including the available triptans at that time in Canada (sumatriptan, rizatriptan, zolmitriptan, and naratriptan) also calculated the NNT [Gawel et al, 2001] and showed similar results to the first two metanalysis. Finally, Ferrari et al published a metanalysis that included 53 clinical trials (12 unpublished) involving 24,089 patients [Ferrari et al, 2001].…”
Section: Selecting a Triptanmentioning
confidence: 70%
“…High responses to placebo are present in trials on treatment with triptans; on adults, trials on triptans record a response to placebo (combined data) ranging from 18% to 35% [31]. Trials on triptans showed a higher placebo effect in children and adolescents than in adults: in children, the response to placebo ranges from 14% to 40% and in adolescents from 25% to 61%.…”
Section: Placebo and Headachementioning
confidence: 99%
“…Within recent years several systematic reviews with metaanalyses of acute migraine treatment have been published [18,19,36,[48][49][50][51][52][53][54]. In addition, three systematic reviews of preventive migraine treatment have been published [48,[55][56][57].…”
Section: Understanding Meta-analysesmentioning
confidence: 99%
“…In addition, three systematic reviews of preventive migraine treatment have been published [48,[55][56][57]. One should distinguish between systematic reviews, where several RCTs of a single drug are evaluated by meta-analysis to get a more precise impression of its merits [49,52,53], and systematic reviews, where several drugs or administration forms of a drug are compared in a meta-analysis [19,36,48,50,52,54].…”
Section: Understanding Meta-analysesmentioning
confidence: 99%